HISTORY AS A SYSTEM OF WRONGS — EXAMINING SOUTH AFRICA'S MARIKANA TRAGEDY IN A TEMPORAL LEGAL CONTEXT (The Strategic Review for Southern Africa, 2020)
On 16 August 2012, striking miners in Marikana, South Africa were fired upon by the South African Police Service, resulting in the death of 44 mineworkers. For many the incident has signalled a turning point for the country. This paper suggests that rather than a turning point, the tragedy at Marikana is perhaps only the newest instalment in a centurylong cycle of industrial action and government violence in South Africa's labour history. Marikana is thus not a turning point, but rather a restatement of the ineffectiveness of law. The article then attempts a theoretical analysis of these events, as well as the matter of whether Marikana is a true event that brings about political and social change. Although many consider Marikana a "founding myth" for a popular uprising in South Africa, the article cautiously suggests that it is in fact just "business as usual".